Skärmning av benledare B250 vid hörselundersökningar - En utvärdering av passiva och aktiva skärmningsmetoder för möjliggörandet av pålitliga mätningar vid benledd hjärnstamsaudiometri för 250 Hz. - Bengtsson, Alicia; Bursell Palm, Hugo; Emteborg Dabrio,, David; Steen, Victoria; Tomasson, Moa; Westerkull, Saga (My University, 2024)
Abstract Auditory Brainstem Response (ABR) utilizes EEG to study the auditory system. When using bone-conducted sound, magnetic fields generated by the bone conductor interfere with the electrode measurements, and therefore air-conducted sound is primarily used. The purpose of this study is to present a method for shielding these aforementioned magnetic fields, particularly those generated by the bone conductor B250 during an ABR examination at 250 Hz. To achieve this objective, the interference was characterized by performing measurements on a watermelon with the following bone conductors: Radioear B71, Radioear B81, and Transducer B250. The watermelon was stimulated at 250 Hz for various sound levels. The results indicated that the interference is repeatable and that its amplitude increases with the stimulation level for all bone conductors. The tests also indicated that the interference generated by B250 is less significant than the interference generated by the other two bone conductors. Three passive shielding methods were then investigated: a wound copper coil, a copper tube without a lid, and a copper tube with a lid. The B250 conductor was positioned in the center of the different configurations, and measurements were taken at various stimulation levels. While all passive methods showed limited effectiveness, the copper coil yielded the best results. Additionally, an active shielding approach was investigated, involving two copper coils: a measuring coil monitoring B250’s interference and an anti-interference coil reducing the impact of the interference on the electrodes. To prevent the magnetic field generated by the anti-interference coil from affecting the measuring coil, a configuration where there is no mutual inductance was required. To find such a configuration, the coils were placed on top of each other with a partial overlap. The configuration was tested by monitoring the generated voltage. The measurement suggested the existence of such a position, and the same study was subsequently conducted in COMSOL multiphysics to determine a more precise theoretical positioning. The COMSOL study resulted in a position where the mutual inductance is zero, indicating that the shielding method is possible.
Keywords: Keywords: Bone conduction, Auditory Brainstem Response, ABR, B250, B71, B81, passive shielding, active shielding, mutual inductance